2014
DOI: 10.1002/ardp.201400255
|View full text |Cite
|
Sign up to set email alerts
|

New CYP17 Hydroxylase Inhibitors: Synthesis, Biological Evaluation, QSAR, and Molecular Docking Study of New Pregnenolone Analogs

Abstract: A new series of pregnenonlone analogs were synthesized and evaluated for their inhibitory activity against cytochrome P450 (CYP17 hydroxylase enzyme). In general, the 5-aryl-1,3,4-thiadiazol-2-yl)-imino-pregnenolone derivatives 11-15 were more active than the sulfonate 24-31 and the ester 37-41 analogs. Derivative 12 showed optimal activity in this series, with IC50 values of 2.5 µM compared with the standard abiraterone (IC50  = 0.07 µM). However, the analogs 11 and 25 showed a better selectivity profile (81.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…The reaction was monitored by TLC (n-hexane:ethyl acetate, 2:3, v:v) [21]. The purity of products were checked by SiO2 column chromatography (5 g) by mixture (MeOH:CHCl3, 3:2, v:v) as elution afforded the pure desired products (Scheme 1).…”
Section: General Procedures For the Synthesis Of 3β-substituted Aryl Ementioning
confidence: 99%
“…The reaction was monitored by TLC (n-hexane:ethyl acetate, 2:3, v:v) [21]. The purity of products were checked by SiO2 column chromatography (5 g) by mixture (MeOH:CHCl3, 3:2, v:v) as elution afforded the pure desired products (Scheme 1).…”
Section: General Procedures For the Synthesis Of 3β-substituted Aryl Ementioning
confidence: 99%
“…Recently, we prepared in our laboratory the iminebenzothiadiazole analogues of pregnenolone molecule [37], aiming to evaluate their cytochrome CYP17 hydroxylase and HIV inhibition activity. In our present work, we have selected β-pregnenolone a starting material for the synthesis of a new series of α-ester of pregnenolone analogues, with inversion in configuration at C-3, by applying of Mitsunobu reaction.…”
Section: Chemistrymentioning
confidence: 99%
“…This pregnenolone derivative was designed as an inhibitor of the enzyme 17α-hydroxylase/C17,20-lyase (CYP17A1) [30,36] which catalyzes two key reactions in steroid hormone biosynthesis. Much more recently, we have synthesized new series of pregnenolone having imino-benzothiazoles 4 at C-20, which showed remarkable inhibition of CYP17 hydroxylase activity, Figure 1 [37].…”
Section: Introductionmentioning
confidence: 99%
“…We are interested in the synthesis and characterization of new steroidal compounds with selective inhibition of CYP17 hydroxylase enzyme properties, for use in the development of more effective treatments of breast and prostate cancer. Building on our previous work [30], in the present study we reported the synthesis of new 17-pregnenoloneimine derivatives with their CYP17 hydroxylase enzyme inhibition activity and the molecular modeling study. …”
Section: Introductionmentioning
confidence: 97%